2022
DOI: 10.1002/adom.202102321
|View full text |Cite
|
Sign up to set email alerts
|

Piezochromic Luminescence of Cyano Substituted E/Z Isomeric Derivatives: Different Responses to External Stimuli

Abstract: As an important class of stimuli‐responsive material, piezochromic organic materials have been widely investigated in recent years. To promote their further applications as pressure sensors, realizing a high sensitivity and big color contrast, especially under high external pressure, is of great importance. Herein, two pure cis/trans isomers, E‐ANTCN and Z‐ANTCN, based on anthracene and cyano substituted double bond are achieved. The molecular structures are determined by nuclear Overhauser effect spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…These results indicate that compound DOPBYN possesses both photoisomerization and photodimerization photoreactions by simple molecular structure regulation, which is a multifunctional photo-responsive molecule compared with other materials comprising the cyanostilbene unit (Table S4, ESI†). 42–45…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicate that compound DOPBYN possesses both photoisomerization and photodimerization photoreactions by simple molecular structure regulation, which is a multifunctional photo-responsive molecule compared with other materials comprising the cyanostilbene unit (Table S4, ESI†). 42–45…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that compound DOP-BYN possesses both photoisomerization and photodimerization photoreactions by simple molecular structure regulation, which is a multifunctional photo-responsive molecule compared with other materials comprising the cyanostilbene unit (Table S4, ESI †). [42][43][44][45] The distinct photo-triggered fluorescence turn-off behaviors along with the photodimerization process are valuable for information encryption. As depicted in Fig.…”
Section: Photodimerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…That is to say, increasing π-π interactions due to the overlapping of anthracene planes intensify excitonic coupling and orbital overlap between neighboring molecules (Figure 3b). Lu et al [29] have reported in 2022 an E/Z isomerism of cyanostilbene derivatives Bis(anthracen-9-yl)phenyl)fumaronitrile (E-ANTCN/Z-ANTCN, Figue 2). Different conformations induce degrees of excited state charge transfer and spatial stacking patterns.…”
Section: Anthracene Derivativesmentioning
confidence: 99%
“…In addition, two E/Z isomers of anthracene and cyano-substituted ethylenes (5E and 5Z ; see the structures of these compounds in Table 1) were synthesized. [89] Upon grinding, both compounds exhibited mechanochromic characteristics. The results of powder X-ray diffractometry (PXRD) investigations indicated that, after grinding treatments, the crystals were almost entirely converted into amorphous solids.…”
Section: Intermolecular Interactions Transformationmentioning
confidence: 99%